A Light-Controlled Allosteric Modulator Unveils a Role for mGlu4 Receptors During Early Stages of Ischemia in the Rodent Cerebellar Cortex - Bossi, Simon; Helleringer, Romain; Galante, Micaela; Monlleó, Ester; Trapero, Ana; Rovira, Xavier; Daniel, Hervé; Llebaria, Amadeu; McLean, Heather (Frontiers in Cellular Neuroscience, 2018)
Metabotropic glutamate receptors (mGlus) are G Protein coupled-receptors that modulate synaptic transmission and plasticity in the central nervous system. Some act as autoreceptors to control neurotransmitter release at excitatory synapses and have become attractive targets for drug therapy to treat certain neurological disorders. However, the high degree of sequence conservation around the glutamate binding site makes the development of subtype-specific orthosteric ligands difficult to achieve. This problem can be circumvented by designing molecules that target specific less well conserved allosteric sites. One such allosteric drug, the photo-switchable compound OptoGluNAM4.1, has been recently employed to reversibly inhibit the activity of metabotropic glutamate 4 (mGlu4) receptors in cell cultures and in vivo. We studied OptoGluNAM4.1 as a negative modulator of neurotransmission in rodent cerebellar slices at the parallel fiber - Purkinje cell synapse. Our data show that OptoGluNAM4.1 antagonizes pharmacological activation of mGlu4 receptors in a fully reversible and photo-controllable manner. In addition, for the first time, this new allosteric modulator allowed us to demonstrate that, in brain slices from the rodent cerebellar cortex, mGlu4 receptors are endogenously activated in excitotoxic conditions, such as the early phases of simulated cerebellar ischemia, which is associated with elevated levels of extracellular glutamate. These findings support OptoGluNAM4.1 as a promising new tool for unraveling the role of mGlu4 receptors in the central nervous system in physio-pathological conditions.